Scale of attitudes towards older adults as learners and users of technology: psychometric evidence - Castro-Rojas, Maria Dolores (2024)
[Objective] Develop and validate a psychometric scale to assess the general population's attitude towards older adults as learners and users of Information and Communication Technologies (PAMTIC scale). [Methodology] A preliminary version of the scale was built based on a systematic review of the literature. In Study 1, the initial version was reviewed by experts and by cognitive interviews.  In Study 2, PAMTIC and the validation scales were applied in digital format to 196 people aged between 18 and 85 years. Exploratory factor analysis (EFA), reliability and validity tests were performed. In studies 3 and 4, the final version of the scale and the validation scales in print and digital formats were applied to 1,041 people aged 18-82 years. In Studies 3 and 4, confirmatory factor analysis (CFA) and reliability and validity tests were performed. [Results] EFA showed 6 factors with good internal consistency coefficients ranging between .80 and .88. CFA confirmed the 6-factor structure and indicated a good fit of the multidimensional model to the data. Correlations between PAMTIC and validation scales provided evidence of nomological validity. [Conclusions] PAMTIC has satisfactory psychometric properties to measure attitude towards older adults as learners and users of Information and Communication Technologies in a reliable and valid way.